2021
DOI: 10.5539/gjhs.v13n2p77
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parental Migration on Health of Left Behind Children

Abstract: After the adoption of liberal economic policy, Nepal entered into the international work force market. Human resource moves abroad seeking for employment opportunities. The globalization of workforce on one hand benefit to the country with a huge amount of inward remittance and on the other brings different bi-products in the country. The physical and emotional effects on the left-behind children [LBC] have come on the forefront as a burning issue. Absence of parents in the family has resulted in children&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Additionally, it is crucial to prioritize the needs of children from poor households, as they are more likely to have migrating parents and caregivers who may have limited education and knowledge about early childhood care [ 29 ]. This study also revealed a correlation between poor ECDI outcomes and children from disadvantaged households, aligning with existing data from LMICs [ 3 , 4 ]. Furthermore, it is important to focus on children whose parents have disabilities, as this study identified a link between poor ECDI outcomes and such cases, particularly when one parent is disable and the other is migrated [ 30 , 31 ].…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Additionally, it is crucial to prioritize the needs of children from poor households, as they are more likely to have migrating parents and caregivers who may have limited education and knowledge about early childhood care [ 29 ]. This study also revealed a correlation between poor ECDI outcomes and children from disadvantaged households, aligning with existing data from LMICs [ 3 , 4 ]. Furthermore, it is important to focus on children whose parents have disabilities, as this study identified a link between poor ECDI outcomes and such cases, particularly when one parent is disable and the other is migrated [ 30 , 31 ].…”
Section: Resultssupporting
confidence: 88%
“…Parental involvement, support, and nurturing are vital for creating a nurturing environment that promotes cognitive, social, and emotional growth [ 1 , 4 , 22 ]. When parents are absent for extended periods, children may experience a deficiency in emotional bonding and have limited opportunities for interactive learning experiences, thus hindering their overall development [ 1 , 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acknowledging the necessity for HRIS within the health sector, Anupam and Sharma (2017) highlight that HRIS saves the health sector the pain of manual administration of patients and employee records which can result in the loss of patient and employee data. The lack of a proper information system in the health sector can cause an unnecessary loss of human lives (Sharma, Devkota, & Acharya, 2021). For instance, in South Africa, a more recent example is the Life Esdimeni tragedy where several mentally ill patients were unlawfully relocated to unregistered care centres which resulted in the death of over…”
Section: Introductionmentioning
confidence: 99%